Radiation Applications (An Advanced Course in Nuclear Engineering,, 2018)
This book focuses on radiation applications in various fields such as industry, environmental conservation, analytical sciences, agriculture, medical diagnosis and therapy, and other areas, from laboratory or research scale to practical or commercial scale. The book targets rather beginning or young professionals in radiation chemistry, processing, biology, and medicine, among others, but also introduces the state of the art of the relevant fields. This volume also helps readers to understand the fundamentals of radiation chemistry, physics, and biology that underlie the miscellaneous applications. Readers will understand, for example, that industry utilizes radiation to fabricate water-absorbent materials or semiconductors and also that cancer patients can be cured through radiation without surgery. These and more facts about radiation applications are made available in this valuable book.